Soft Factor In the Implementation of Quality Management Program in Majlis Agama Islam Selangor (MAIS) (Sains Humanika, 2018)
Many studies on the implementation of quality management programs were carried out by previous researchers. However, the study on the soft or human factors in the implementation of quality management programs is still poorly explored. Therefore, this article aims to analyze soft factors in the implementation of quality management programs at Selangor Islamic Religious Council or Majlis Agama Islam Selangor (MAIS). This study uses a qualitative method involving MAIS as a case study. Semi-structured interviews were used as a data collection method and supported by relevant documents collected from MAIS. A total of fifteen informants comprising top management and MAIS officers were interviewed to obtain in-depth information on the subjects studied. The findings reveal that there are six soft factors emerged in the implementation of quality management programs at MAIS namely leadership, training and development, teamwork, customer focus, Syura and rewards. This study demonstrates that soft factors has helped facilitate the implementation of quality management programs in MAIS. The results of this study can be used as guidance by managers in public or corporate organizatons in their efforts to implement quality management programs effectively.
Keywords: Soft factor; implementation; quality management; majlis agama islam selangor; qualitative